A Misguiding Osteoid Osteoma in the Bicipital Tuberosity of the Radius - Konstantinos Ditsios; Nikolaos Papadakis; Ioannis Theodoroudis; Lazaros Kostretzis; Panagiotis Konstantinou; Iosafat Pinto; Anastasios Christodoulou (Case Reports in Orthopedics)
Osteoid osteoma is a benign bone tumor that appears most frequently in young patients. It is more common in males and it concerns mostly the long bones of the lower limb. A 20-year-old young woman presented to our outpatient department with pain in her left elbow. The symptoms began four years ago. At first, her symptoms were attributed to ulnar neuritis, confirmed by nerve conduction studies. In the following two years, she had undergone two surgical operations for decompression of the ulnar nerve. As a result, she reported poor results, which forced her to take frequently anti-inflammatory drugs for some years. When the patient presented to us, we planned a three-phase bone scan and an elbow MRI, which revealed the lesion. Based on the image findings of osteoid osteoma, we proceeded to the surgical removal of the tumor. Since then, the patient is pain-free and has a full range of motion of the affected elbow. Osteoid osteoma usually mimics multiple pathologies in the upper limb especially joint disease posing a challenge for the physician. The diagnosis requires high index of suspicion and a prompt diagnostic and surgical management.